Environmental control of malting barley response to nitrogen in the Pampas, Argentina - Prystupa, Pablo (2018)
Twenty five single-year field experiments were established in order to assess the effects of nitrogen fertilization on grain yield, size, and protein concentration, and to explain its response to fertilization with soil, climate, and crop management variables easy to collect. While grain yield in control treatments was positively related to rainfall during the full crop cycle and negatively related to temperature during the critical period previous to heading, grain yield response to nitrogen was positively related with the product of fertilizer nitrogen rate by rainfall. Grain protein concentration response to nitrogen fertilization was positively related to fertilizer nitrogen rate and negatively related soil nitrate. It is worth noting that the effect of N fertilization on grain protein concentration was not conditioned by rainfall. We could establish that grain protein concentration was determined by the ratio between nitrogen availability (soil nitrogen-nitrate at sowing plus nitrogen added as fertilizer) and grain yield.